CKBiology: An Active Learning Curriculum Design for Secondary Biology - Acosta, Alisa; Slotta, James D. (Frontiers in Education, 2018)
This research paper presents the design of an active learning curriculum and corresponding software environment called CKBiology, reporting on its implementation in two sections of a Grade 12 Biology course across three design cycles. Guided by a theoretical framework called Knowledge Community and Inquiry (KCI), we employed a design-based research methodology in which we worked closely with a high school biology teacher and team of technology developers to co-design, build, test, implement, and revise this curriculum within a blended learning context. We first present the results of a needs assessment and baseline analysis in which we identify the design constraints and challenges associated with infusing a ‘traditional’ Grade 12 Biology course with a KCI curriculum. Next, we present the design narrative for CKBiology in which we respond to these constraints and challenges, detailing the activity sequences, pedagogical aspects, and technology elements used across three design iterations. Finally, we provide a qualitative analysis of student and teacher perspectives on aspects of the design, including activity elements as well as the CKBiology interface. Findings from this analysis are synthesized into design principles which may serve the wider community of active learning researchers and practitioners.